PERUBAHAN KELEMBAGAN PENDIDIKAN DALAM PENINGKATAN MUTU PENDIDIKAN ISLAM di PP. TEBUIRENG JOMBANG dan PP. LIRBOYO KEDIRI - Hakim, Lukman (Al Tadib : Jurnal Ilmu Pendidikan, 2022)
This study aims to find changes in Islamic boarding school education institutions, from institutions that are managed in a salaf (traditional) manner with their activities, into educational institutions that have changed their management to become kholaf (modern). As is known, Islamic boarding schools are Islamic educational institutions as well as a place for the spread of Islam in its early existence. The salaf (traditional) system, all activities and teaching materials are sourced directly from the kiai as the leader of the Islamic boarding school. Along with the passage of time and the times, the boarding school has changed from various aspects, including the institutional aspect of salaf (traditional) with the existence of a national curriculum that is included in learning activities, human resources, buildings, and the boarding school institutional management system that is open with leadership. more delegative. In this study focused on the orientation of educational institutional changes, management of changes in educational institutions, and the implications of changes in educational institutions in two places, namely Pondok Pesantren Tebuireng Jombang and Pondok Pesantren Lirboyo Kediri.